(untitled) (Third Sector Social Economic Review, 2016)
Consumers may not have the necessary information to evaluate the quality of all the products and services in the market. In today’ market where too many technological products are offered, it is very difficult to evaluate the quality of products. Quality certificates guides the consumers at this point.This certificate proves the conformity of the products to the special standarts, specifications, technical and esthetical features and conditions under the control of specialists. This study is planned and carried out to determine the acceptance and adoption level of quality certificates by consumers in the context of protection of consumer rights and maximization of consumer satisfaction.